The use of glass transition temperature in forecasting of whey powder storage stability, obtained with the use of electro-spark treatment - Kochubei-Lytvynenko, Oksana; Mikhailik, Vyacheslav; Ukrainets, Anatoliy (My University, 2016)
This study investigated the behavior during storage of dry whey obtained using different approaches that prevent caking (adding silicon dioxide, electro-spark treatment of whey). Forecasting the stability of quality whey powder was carried out based on a glass transition temperature.We showed that the highest glass transition temperature (+18.5 °С) and, subsequently, smallest difference between product temperatures and glass transition temperature were discovered in dry whey, obtained with the use of electro-spark treatment, which proves its stability while in storage.We found that the other samples of dry whey under normative storing terms (from 0 till 20 °С) are predominantly in rubbery state, which can negatively influence on stability of the product while in storage. Based on the glass transition temperature we determined that electro-spark treatment in technology of whey powder allowed reaching anti-caking effect due to physicochemical processes resulting from electro-spark charges. This was proved by calculationstickiness and caking sensibility index and the degree of caking (to 2 %).
Keywords: whey powder; electro-spark treatment; glass transition temperature; caking; stickiness and caking sensibility index; суха молочна сироватка; електроіскрова обробка; температура склування; налипання; злежування; сухая молочная сыворотка; электроискровая обработка; температура стеклования; налипание; слеживание; кафедра технології молока і молочних продуктів; кафедра технології оздоровчих продуктів